Mars Methane Sources in Northwestern Gale Crater Inferred From Back Trajectory Modeling - Y. Luo (American Geophysical Union (AGU), 2021)
Abstract During its first seven years of operation, the Sample Analysis at Mars Tunable Laser Spectrometer (TLS) on board the Curiosity rover has detected seven methane spikes above a low background abundance in Gale crater. The methane spikes are likely sourced by surface emission within or around Gale crater. Here, we use inverse Lagrangian modeling techniques to identify upstream emission regions on the Martian surface for these methane spikes at an unprecedented spatial resolution. Inside Gale crater, the northwestern crater floor casts the strongest influence on the detections. Outside Gale crater, the upstream regions common to all the methane spikes extend toward the north. The contrasting results from two consecutive TLS methane measurements performed on the same sol point to an active emission site to the west or the southwest of the Curiosity rover on the northwestern crater floor. The observed spike magnitude and frequency also favor emission sites on the northwestern crater floor, unless there are fast methane removal mechanisms at work, or either the methane spikes of TLS or the non‐detections of ExoMars Trace Gas Orbiter cannot be trusted.